Call for Emergency Action to Limit Global Temperature Increases, Restore Biodiversity, and Protect Health: Wealthy Nations Must do Much More, Much Faster. (6th September 2021) - Atwoli, Lukoye; Baqui, Abdullah H.; Benfield, Thomas; Bosurgi, Raffaella; Godlee, Fiona; Hancocks, Stephen; Horton, Richard; Laybourn-Langton, Laurie; Monteiro, Carlos; Norman, Ian; Patrick, Kirsten; Praities, Nigel; et al.
Joint editorial calling for emergency action to limit global temperature increases, restore biodiversity, and protect health.